Trend Penelitian Kemiskinan di Provinsi Jawa Tengah 2020-2025: Analisis Bibliometrik - Muhammad Banyu Gusti Nugroho; Muhammad Billy Ridiansyah; Muhammd Wijdan nabil; Anisa Ika Aprilia (E-Jurnal Kajen, 2025)
This study aims to map and analyze research trends on poverty in Central Java Province using a bibliometric approach with VOSviewer software. Through keyword network analysis, the study identifies dominant themes, temporal dynamics, and interconnections among topics within the scientific literature on poverty. The visualizations reveal that poverty in Central Java is influenced not only by economic factors but also closely linked to health, education, gender, and regional inequality. The analysis also highlights emerging topics such as the role of the state and household income in recent academic discourse. These findings enrich the conceptual understanding of poverty and provide an empirical basis for designing more inclusive and evidence-based poverty alleviation policies. Therefore, this study makes a significant contribution to the development of relevant and sustainable development strategies.